Status of Iodine Intake and Comparison of Characteristics according to Iodine-sourced Food Intake Patterns of Chinese Adults: A Study Encompassing Three Regions with Different Iodine Nutritional Statuses - Danying Zhang; Ho Kyung Ryu (Korean Journal of Community Nutrition, 2022)
Objectives: This study examines the status of iodine intake and compares the characteristics (region and thyroid disease prevalence) according to the iodine-sourced food intake pattern in Chinese adults.